Keterhubungan Ruang Permukiman Tradisional di Desa Sukarara Berlandaskan Nilai-Nilai Nyensek dan Begawe - Yunianti, Sri Rahmi; Sudaryono, Sudaryono; Iskandar, Doddy Aditya (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2018)
Culture changes in community will affect its social structure (Hirsan, 2005). Additionally, Auliya (2009) said that cultural changes also determine the elements of residential. Social culture changes not only will influence the order of settlement space but also the concept of spatial structure. Sukarara Village as one of tourism destination for handicraft weaving in Lombok Tengah Regency has changed, especially in settlement physic. There was six traditional house type but remain four types, which mixed with modern buildings. Physically, settlement building seen using modern element; however, the community has strong belief on cosmologic value, which implemented in settled rules and tradition. This study is to find out the connectedness in the phenomena between developments of an increasingly modern society with rules and tradition belief to settle; how integration and pattern formed in Sukarara Village. This research used qualitative inductive method, which approached with phenomenology technique using in-depth interview in Sukarara Vilage. The result shows that there are four kinds of integration and pattern concept in Sukarara Village: (1) bale beleq as spatial shaping : connectedness history; (2) nature as sacred clue to settle: connectedness community culture; (3) various type and building shape as settlement pattern transformation: connectedness spatial physic; (4) farming and weaving as living basic: connectedness of source of life. The four concepts change pattern orientation in traditional settlement, which is adapted by community along live activity, nyensek and begawe.